The implications of carbon dioxide and methane exchange for the heavy mitigation RCP2.6 scenario under two metrics. Issue 51 (August 2015) - Huntingford, Chris; Lowe, Jason A.; Howarth, Nicholas; Bowerman, Niel H.A.; Gohar, Laila K.; Otto, Alexander; Lee, David S.; Smith, Stephen M.; den Elzen, Michel G.J.; van Vuuren, Detlef P.; Millar, Richard J.; Allen, Myles R.
Highlights: Exchanging methane for carbon dioxide emissions affects peak global warming. Economic constraints severely affects exchange possibilities. Chosen metric determines if economic to eliminate all removable methane emissions. If all methane emissions could be removed, this could aid meeting two-degrees warming target. Abstract: Greenhouse gas emissions associated with Representative Concentration Pathway RCP2.6 could limit global warming to around or below a 2 °C increase since pre-industrial times. However this scenario implies very large and rapid reductions in both carbon dioxide (CO2 ) and non-CO2 emissions, and suggests a need to understand available flexibility between how different greenhouse gases might be abated. There is a growing interest in developing a greater understanding of the particular role of shorter lived non-CO2 gases as abatement options. We address this here through a sensitivity study of different methane (CH4 ) emissions pathways to year 2100 and beyond, by including exchanges with CO2 emissions, and with a focus on related climate and economic advantages and disadvantages. Metrics exist that characterise gas equivalence in terms of climate change effect per tonne emitted. We analyse the implications of CO2 and CH4 emission exchanges under two commonly considered metrics: the 100-yr Global Warming Potential (GWP-100) and Global Temperature Potential (GTP-100). This is whilst keeping CO2 -equivalent emissions pathways fixed, based on the standard set of emissions usually associated with RCP2.6. An idealised situation of anthropogenic CH4 emissions being reduced to zero across a period of two decades and with the implementation of such cuts starting almost immediately gives lower warming than for standard RCP2.6 emissions during the 21st and 22nd Century. This is despite exchanging for higher CO2 emissions. Introducing Marginal Abatement Cost (MAC) curves provides an economic assessment of alternative gas reduction strategies. Whilst simpler than utilising full Integrated Assessment Models (IAMs), MAC curves are more transparent for illustrative modelling. The GWP-100 metric places a relatively high value on climate change prevented for methane emission reduction, as compared to an equivalent mass of CO2 reduction. This in combination with the strong non-linearity in MAC curves (moving quickly from relatively cheap removal to emissions difficult to cut at any cost) causes little change under cost minimisation from standard RCP2.6 emissions. This reflects the original development of RCP2.6 standard emissions from similar minimisation. With gas exchange under GTP-100, however, we find much less methane is abated, resulting in higher temperatures, whilst costs are slightly lower. Our results also highlight the point at which greater methane mitigation would become beneficial from both a climate and economic aspect. If by 2030 removal of all methane were to become possible at an average cost less than 1000 per tonne of CH4, then this would be the cheapest option, for GWP-100 metric and our CO2 MAC curve. Critically this would increase the possibility of constraining warming to two degrees.